Suicidal ideation, attempt and associated factor among secondary school students in Harari regional state, Eastern Ethiopia. A multi-center cross-sectional study - Bete, Tilahun; Birhanu, Abdi; Negash, Abraham; Yadeta, Elias; Lemi, Magarsa; Balcha, Tegenu; Sertsu, Addisu; Birhanu, Bekelu; Nigussie, Shambel; Gemechu, Kabtamu; Meseret, Fentahun; Mohammed, Hanan; et al. (Frontiers in Psychiatry, 2023)
Background: Currently, Suicide become a major public health issue across the globe. It is the second-leading cause of death for adolescents. Even though the suicide rate increased, there is no study conducted to investigate the determinants of suicide in the study area. Therefore this study aimed to assess the magnitude of suicidal ideation, attempt, and associated factor among secondary school students in Harari regional state, Eastern Ethiopia, 2022. Methods; A institutional-based cross-sectional study was conducted among randomly selected 1666 secondary school students. A structured-self-administered questionnaire was used for data collection. Composite International Diagnostic Interview (CIDI) was used to assess suicidal ideation and attempt. Depression Anxiety and Stress Scale were also used to assess depression anxiety and stress respectively. Data were entered into Epi Data version 3.1 and exported to Stata Version 14.0 for analysis. Logistic regression analysis was done to determine the association between the outcome and independent variables and the statistical significance was declared at a p-value of <0.05. Result; The overall magnitude of suicidal ideation and attempts was 13.82% at 95% CI (12.16-15.66) and 7.61% at 95% CI (6.37-9.07) respectively. Suicidal ideation and attempt were significantly associated with having depressive symptoms (AOR = 1.54 (95% CI, 1.08-2.19)) and (AOR =2.37 (95% CI, 1.46-3.86)), having anxiety symptoms (AOR =1.80 (95% CI, 1.25-2.59)) and (AOR =1.89 (95% CI, 2.14-10.65)) being exposed to sexual violence (AOR =3.36 (95% CI, 1.65-6.84)) having a family history of suicidal attempt (AOR =2.12 (95% CI, 1.21-3.69)) and (AOR =4.74 (95% CI, 2.14 -10.65)) respectively, Whereas living in a rural residence (AOR =1.65 95% CI, 1.08-2.55)) was significantly associated with suicidal attempts. Conclusions and Recommendations: Nearly one in six secondary students had both suicidal ideation and an attempt. Suicide is one of the psychiatric emergencies that need immediate action. So the concerned body from either a governmental or non-governmental organization should work in setting strategies to minimize sexual violence, and depressive and anxiety symptoms.